The Influence Of Gender Role Conflict, Loneliness, And Father Involvement On Subjective Well-Being Among Male University Students - Brahmana, Karina Meriem Beru; Silaban, Rifaldi Partogi; Simalango, Yohana Stefani; Siregar, Theresia Naftalia Br (STABN RADEN WIJAYA WONOGIRI, 2025)
This study examines the influence of gender role conflict, loneliness, and fatherless on the subjective well-being of male university students in Indonesia, a population that faces unique psychosocial demands during the transition from adolescence to emerging adulthood. The increasing tension between traditional masculine norms—emphasizing emotional restraint, autonomy, and strength—and contemporary expectations that value emotional openness and social connectedness may place male students at heightened risk for lower well-being. Using a quantitative correlational design, this research involved 227 male students selected through purposive sampling. Four standardized instruments were employed: The Gender-Role Conflict Scale, the Revised UCLA Loneliness Scale, the Fatherhood Scale, and two well-being measures (SWLS and SPANE). Data were analysed using SEM-PLS to assess the simultaneous and relative contributions of each predictor. Results indicate that loneliness and fatherless significantly and negatively predict subjective well-being, with loneliness emerging as the strongest predictor. In contrast, gender role conflict does not significantly influence subjective well-being in this sample. The model explains 26.9% of the variance in subjective well-being, supported by robust regression diagnostics, including acceptable VIF values and the absence of heteroskedasticity. These findings highlight the central role of emotional and relational factors—particularly loneliness and the presence of a supportive father figure—in shaping well-being among male students. The nonsignificant effect of gender role conflict suggests that masculine norm pressures may not directly reduce well-being but could influence it indirectly through other psychological mechanisms. The study underscores the need for university counselling services and family-based interventions to address loneliness and strengthen father–son relationships as protective factors that can enhance the psychological well-being of male students